Levo Vladimirovo darbų įtaka mokslininkams (apklausos metodo taikymas) - Macevičiūtė, Elena (Knygotyra, 2002)
The main purpose of the article is to test the application of an open-ended questionnaire for collecting the data and the valuation of the scholarly heritage. The peer-review is a legitimate way of the assessment of the contribution into science by individual scholars or institutions. However, it is rarely conducted in a form of the answering to an open-ended questionnaire. The author has used the method to collect the opinions of Lithuanian and foreign researchers about the pasi, present, and future influence of Levas Vladimirovas works on the development of Lithuanian book bistory, book science, library and information science, or information society research. The data collected by this method was compared to the data that was collected to assess the significance of L. Vladimirovas works by other methods: bibliographic, bibliometric, funding allocation, biographic reviews, teacher-student genealogy, etc. The qualitative results collected by an open-ended questionnaire from l 8 respondents (mainly Lithuanian humanitarian and social scientists) were analysed using the historical categories of the past, present and future and the subject categories characterising the field of information and communication sciences. The results are comparable to the ones received by other methods. Besides, an array of opinions allows one predict the future influence of the scientific heritage, the emotional subjective responses provide data that is usually revealed only in memoirs. The case of L. Vladimirovas is a specific one as the people who knew him well are still alive, but they are not influenced by any factors that would accompany the assessment of a living scholar. Whether the method would be valid in the cases of persons diseased long-time ago also remains unclear.